Ser irmã(ão) de criança com asma ou bronquite na perspectiva hermenêutica de Gadamer - Matos, Ana Paula Keller de (2014)
Asthma is one of the most common chronic diseases and its prevalence is increasing, especially among children. The care demands from this situation impacts the entire family, with repercussions in several of its members, including the sibling. Therefore, this work aimed to understand the sibling s experience that lives with children with asthma or bronchitis on the voice of the sibling. It is an exploratory, qualitative research, based on the theoretical and methodological framework of Gadamer s philosophical hermeneutics. Philosophical hermeneutics seeks understanding, the apprehension of the senses through horizons that are mediated through dialogue with the purpose of understanding. And the understanding demands to face the fore-meanings and prejudices about the phenomenon that is about to be understood. This process involves language, which makes it possible to achieve understanding of the being. The language allows consciousness of being affected by history, where it is noted that the past is always present in human thoughts in order to be revealed through dialogue. It is the dialogue that there is the true birth of the truth. Eight children and teenagers, older siblings of children with asthma or bronchitis, ages six to 16 years old were the participants of this study. Data collection was done through open interviews integrated to the strategies of drawing, letter or photograph. Five steps proposed by researchers in Glasgow were followed, where is adopted the Gadamer's perspective as a framework for data analysis. The dialogue analysis allows understanding that siblings appreciates the fraternal relationship and overrides the effects of the child s asthma or bronchitis in his/her life. Union, fellowship, friendship and protection mark the relationship between siblings, where the mere presence of the child in the sibling s life is understood as happiness. In their daily lives, the siblings are engaged in actions of care and protection to the chronic ill child that is determined by the dynamics of the family. In this situation, they count on few sources of information about the child's illness and wish for having more information about it. They take responsibilities for the child s care such as give medicine, keep vigil, take care of the environmental and try to prevent possible risks that may exacerbate the disease. They feel that parents treat them and the sick child differently. And although they have their own demands, those are not perceived and coping is held in solitary way, sustained by the action to consider its own situation and find nurturing for what makes them suffer. This process allows the sibling to understand his/her life as "normal". The findings highlight the invisibility of the sibling of children with asthma or bronchitis, which implies a need for professional practice transformation aiming a comprehensive, meaningful and complete care. That requires changes in teaching, training and research scenarios. There is no way to care in a complete and humane way walking paths that are "straight" or " predetermined " and absents of fusions of horizons, without opening to the encounter with other through dialogue.